Representation of Residential Socio-Spatial Segregation (Case Study: Parasite Movie) - Novianti , Yenny; Rengganis, Anandita; Hendra (Jurnal Koridor, 2025)
Architecture and film are two disciplines that are closely intertwined in discussing and visualising a space. Film cannot stand alone without architecture, architecture plays a role in building space in film by being used to convey stories, shape perceptions, and depict social reality. This research will examine the depiction of socio-spatial separation in Parasite and compare it with the physical setting of the area in Seongbuk-dong and Ahyeon-dong, Seoul, South Korea. The research method used is descriptive qualitative analysis using a semiotic approach. The results show that the film Parasite effectively depicts the contrasting differences between decent neighbourhoods and slums in terms of geography, land use, settlement quality, and accessibility. Seongbuk-dong, an aristocratic neighbourhood, offers high-quality facilities and easy access, while Ahyeon-dong, a slum, has low-quality services and limited accessibility. The conclusion of this study confirms that architecture in film has an important role in reflecting and critiquing social phenomena such as socio-spatial segregation, and emphasises the importance of more inclusive urban planning in reducing social inequality